QT PRODACT: In Vivo QT Assay in Anesthetized Dog for Detecting the Potential for QT Interval Prolongation by Human Pharmaceuticals - Hiroyuki Tashibu; Hiroyasu Miyazaki; Kumiko Aoki; Yasuki Akie; Keiji Yamamoto (Elsevier, 2005)
The purpose of this study was to assess the utility of the isoflurane-anesthetized dog model for detecting the potential for QT interval prolongation by human pharmaceuticals. The effects of 10 positive compounds with torsadogenic potential, 8 negative compounds with little torsadogenic potential, and dl-sotalol as a common positive compound were evaluated in 5 facilities in accordance with the common protocol approved by QT PRODACT. Each test compound was cumulatively infused into male beagle dogs anesthetized with isoflurane. Surface lead II ECG, blood pressure, and plasma concentrations for the positive compounds were measured. Repeated administration of the vehicle examined in each facility before the start of the experiments resulted in a slight, but not significant, change in corrected QT (QTc) interval, indicating that this model only shows slight experimental variation. Although an inter-facility variability in the extent of dl-sotalol-induced QT interval prolongation was observed, dl-sotalol significantly prolonged QTc interval in all facilities. All positive compounds significantly prolonged QTc interval at plasma levels up to 10 times those in patients who developed prolonged QTc interval or TdP, whereas no negative compounds did so. These data suggest that the in vivo QT assay using the anesthetized dog is a useful model for detecting the potential for QT interval prolongation by human pharmaceuticals.Supplementary material (Appendix): available only at http://dx.doi.org/10.1254/jphs.QT-A3 Keywords:: anesthetized dog, QT interval, safety pharmacology